A Crack in an Anisotropic Layered Material - Clements, D.L. (Engineering Transactions, 1979)
The problem of determining the stress and displacement fields round a crack in an anisotropic layered material is considered. The problem is reduced to a system of three simultaneous Fredholm integral equations which are solved numerically in certain cases. In particular, the case when the material containing the crack is strongly anisotropic is examined in some detail.